Diamond and negative expansion particle reinforced aluminum matrix composite and preparation method

By regulating the volume fraction of diamond and negative expansion particles, diamond and negative expansion particles reinforced aluminum-based composite materials with excellent thermal physical properties were prepared, which solved the problem of mismatch in the thermal expansion coefficient of traditional composite materials, and achieved thermal expansion coefficient matching with semiconductor materials and efficient thermal conductivity.

CN119592858AActive Publication Date: 2025-03-11UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411805352.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-11
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The thermal expansion coefficient of traditional metal-based composite materials does not match the semiconductor materials, resulting in thermal stress problems and affecting the reliability and durability of the material.

Method used

By regulating the volume fraction of diamond and negatively expanded particles, diamond and negatively expanded particles reinforced aluminum-based composites with excellent thermal physical properties were prepared, and the strategy was optimized in concert to match the thermal expansion coefficient of semiconductor materials.

Benefits of technology

The thermal expansion coefficient matching the semiconductor material is achieved, the thermal conductivity and density of the composite material is improved, the thermal expansion coefficient is reduced, and the thermal physical properties and reliability of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592858A_ABST
    Figure CN119592858A_ABST
Patent Text Reader

Abstract

The invention provides a diamond and negative expansion particle reinforced aluminum matrix composite and a preparation method, and belongs to the technical field of composites. The aluminum-based composite material is composed of a diamond phase and a negative thermal expansion phase which are dispersed in an aluminum matrix. The average particle size of the diamond phase is 10-1000 [mu] m, and the ratio of the average particle size of the diamond phase to the average particle size of the negative thermal expansion particles is 10-20; the particle size of the negative thermal expansion particles adjacent to the diamond phase is smaller than that of the negative thermal expansion particles away from the diamond phase. The diamond and negative expansion particle reinforced aluminum-based composite material with excellent thermophysical performance is obtained by regulating and controlling the volume fraction of the diamond and the negative expansion particles, the thermal expansion coefficient matched with a semiconductor material is prepared through a collaborative optimization strategy, and the diamond and negative expansion particle reinforced aluminum-based composite material is applied to the field of electronic packaging heat dissipation materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and particularly relates to a diamond and negative expansion particle reinforced aluminum-based composite material and a preparation method thereof. Background Art

[0002] The thermal expansion coefficients of traditional metal-based composite materials do not match those of semiconductor materials such as silicon, germanium, and gallium nitride. In electronic packaging, aerospace, and optical equipment, temperature changes are a serious problem that causes thermal stress. When the thermal expansion coefficient of a material does not match that of the surrounding environment, temperature changes can cause stress inside the material, resulting in cracks and breakage. Negative expansion materials can effectively solve the problem of thermal stress. Negative expansion materials can provide thermal expansion characteristics opposite to those of the surrounding materials, reduce or even offset thermal stress between materials, and thus improve the reliability and durability of the overall structure.

[0003] Diamond has high hardness, chemical stability, high light transmittance, isotropic thermal conductivity, and its thermal conductivity can reach 2000W / mK, while the thermal expansion coefficient is only 1.5×10 -6 / K, it is an ideal heat dissipation material. In recent years, artificially synthesized diamond particles have the characteristics of simple process and low cost, and have become ideal metal matrix composite reinforcement. The thermal expansion coefficient of negative expansion particles has a large control range and excellent negative expansion performance. It can suppress the positive thermal expansion coefficient of the metal matrix, thereby obtaining a composite material with a lower thermal expansion coefficient. Metal aluminum and aluminum alloys have good processing properties, mechanical properties, high thermal conductivity and other characteristics. Negative expansion particle reinforced aluminum matrix composites and diamond reinforced aluminum matrix composites have been reported, but there is still room for optimization in the performance control of these composite materials. For example, the intrinsic low thermal conductivity and high volume fraction agglomeration of negative expansion particles will greatly reduce the thermal conductivity of low expansion aluminum matrix composites; and there is an interface reaction between diamond and aluminum matrix, resulting in weak bonding ability at the interface of the composite material, which seriously limits the thermal physical properties of the composite material. On the other hand, interface gaps are easily formed at the interface during the cooling process, thereby forming a large interface thermal resistance, affecting the effective heat conduction of the composite material, reducing the density of the composite material, and limiting the control range of the thermal expansion coefficient of the composite material. The Chinese invention patent with publication number CN114411010A discloses a method for manufacturing a low-expansion diamond-reinforced aluminum-based composite material. However, the thermal expansion coefficient of the composite material is as high as 6ppm, which is still different from the thermal expansion coefficient of the Si chip. In addition, advanced semiconductor materials have fast hot start and many cycles, and the mismatch between the thermal expansion of the packaging material and the chip will cause the device to crack. Therefore, the preparation of negative expansion and diamond hybrid reinforced aluminum-based composite materials has high thermal conductivity and low thermal expansion coefficient, and increases the control range of the thermal expansion coefficient of the composite material, which has important scientific and engineering significance. Summary of the invention

[0004] To solve the above problems, the present invention provides a diamond and negative expansion particle reinforced aluminum-based composite material and a preparation method. By adjusting the volume fraction of diamond and negative expansion particles, a diamond and negative expansion particle reinforced aluminum-based composite material with excellent thermophysical properties is obtained. Through a collaborative optimization strategy, a thermal expansion coefficient matching that of semiconductor materials is prepared and applied to the field of electronic packaging heat dissipation materials.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] On the one hand, the present invention provides a diamond and negative thermal expansion particle reinforced aluminum-based composite material, wherein the aluminum-based composite material consists of a diamond phase and a negative thermal expansion phase dispersed in an aluminum matrix; the average particle size of the diamond phase is 10-1000 μm, and the ratio of the average particle size of the diamond phase to the average particle size of the negative thermal expansion particles is 10-20; the particle size of the negative thermal expansion particles adjacent to the diamond phase is smaller than the particle size of the negative thermal expansion particles away from the diamond phase.

[0007] Furthermore, the volume fraction of the diamond phase is 30-80%; the volume fraction of the negative thermal expansion ceramic phase is 10%-40%, and the volume fraction of the aluminum matrix is ​​at least 10%.

[0008] Furthermore, the negative thermal expansion phase is ZrW2O8, Cu2P2O7, Cu2V2O7, PbTiO3, ZrMo2O8, Mn3Zn 1- x Sn x N or Mn3Zn 1-x Ge x One or more of N, 0 <x<1。

[0009] Furthermore, the aluminum matrix is ​​pure aluminum or an aluminum alloy.

[0010] Furthermore, the particle size range of the negative thermal expansion particles adjacent to the diamond phase is not greater than 0.5 μm.

[0011] On the other hand, the present invention provides a method for preparing the above-mentioned diamond and negative thermal expansion particle reinforced aluminum-based composite material, comprising weighing diamond powder, negative thermal expansion particles and aluminum matrix material according to a proportion; mixing the diamond powder and the negative thermal expansion particles and placing them in a graphite mold, compacting them, and placing the aluminum matrix material above the graphite mold; vacuum heating and melting the graphite mold, and performing pressurized heat preservation treatment after keeping the temperature for a preset time; and cooling the mold after the pressurized heat preservation treatment is completed.

[0012] Furthermore, the average particle size of the diamond powder is 10-1000 μm; and the ratio of the average particle size of the diamond phase to the average particle size of the negative thermal expansion particles is 10-20.

[0013] Furthermore, D5 of the negative thermal expansion particles is not greater than 0.5 μm.

[0014] Furthermore, the vacuum heating process is as follows: the vacuum degree of the smelting furnace is ≤1Pa, the heating rate is 20-80°C / min, and the temperature is kept at Tm-Tm+150°C for 20-70min, wherein Tm is the melting point of the aluminum matrix.

[0015] Furthermore, the process of the pressurized heat preservation treatment is: using inert gas to pressurize to 0.5-2.5Mpa, and heat and pressure preservation at Tm-Tm+150°C for 10-60min, wherein Tm is the melting point of the aluminum matrix.

[0016] The beneficial effects brought by the technical solution provided by the embodiment of the present invention include:

[0017] 1. The present invention mixes diamond and negative thermal expansion particles, effectively reducing the thermal expansion performance of the composite material and increasing the interface bonding force. The matrix metal is pure aluminum or aluminum alloy, so that the composite material maintains good mechanical properties and thermal conductivity. During the composite process, since the negative thermal expansion particles also inhibit the expansion of the aluminum matrix, the phenomenon of mismatch between the thermal expansion coefficients of diamond and the aluminum matrix is ​​improved, and the thermal expansion coefficient of the diamond aluminum composite material is further reduced.

[0018] 2. The present invention uses a gas pressure infiltration process to keep the solid-phase mixed reinforcement and the solid-phase metal matrix in full contact under high pressure, and the aluminum matrix melts at high temperature, so that the molten aluminum matrix is ​​fully pressed into the pores of the diamond and the negative thermal expansion particles, ensuring the high density of the diamond-mixed negative thermal expansion particles / aluminum-based composite material. At the same time, this preparation process can control the infiltration temperature, pressure and time to avoid the interface reaction between the two phases to the greatest extent. Due to the high density of the prepared composite material, this preparation process can solve the defects of internal looseness, pores, etc. in composite materials prepared by other processes. Due to the vacuum condition, the oxidation of aluminum metal during the reaction process can be effectively avoided, ensuring the purity of the prepared negative thermal expansion particles + diamond hybrid reinforced aluminum-based composite material. Due to the high pressure condition, the heat preservation and pressure maintenance can make the interface bonding between the metal and the diamond negative thermal expansion particles more firm, and the elastic modulus and strength of the obtained negative thermal expansion particles + diamond hybrid reinforced aluminum-based composite material are increased.

[0019] 3. The synthesis procedure of the negative thermal expansion particle + diamond hybrid reinforced aluminum-based composite material prepared by the present invention is simple and flexible, the equipment used has low investment cost, and the preparation process is simple, the raw material price is low, the matrix pure aluminum or aluminum alloy source is widely available and easy to obtain, and the cost is low, so that the composite material has a very broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 This is a SEM image of the diamond and negative expansion particle reinforced aluminum-based composite material prepared in Example 1 of the present invention;

[0022] Figure 2 This is the thermal expansion curve of the diamond and negative expansion particle reinforced aluminum-based composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0024] An embodiment of the present invention provides a diamond and negative thermal expansion particle reinforced aluminum-based composite material, wherein the aluminum-based composite material consists of a diamond phase and a negative thermal expansion phase dispersed in an aluminum matrix; the average particle size of the diamond phase is 10-1000 μm, and the ratio of the average particle size of the diamond phase to the average particle size of the negative thermal expansion particles is 10-20; the particle size of the negative thermal expansion particles adjacent to the diamond phase is smaller than the particle size of the negative thermal expansion particles away from the diamond phase.

[0025] In the present invention, the aluminum matrix is reinforced by using diamond phase and negative thermal expansion phase. The diamond phase has a high thermal conductivity and a low expansion coefficient. However, there are corresponding problems in the composite of diamond and aluminum matrix. The poor wettability between diamond and aluminum liquid leads to cracks easily occurring at the interface between the diamond phase and the aluminum matrix in the subsequent deformation process of the prepared composite material. In the prior art, the surface of diamond is usually treated to improve its bonding strength with the aluminum matrix. In this application, by adding negative thermal expansion particles with a certain particle size, the wettability between the aluminum matrix and the surface of diamond particles can be improved. On the other hand, there are also corresponding problems in the composite of negative thermal expansion particles and the aluminum matrix. Since the negative thermal expansion particles and the aluminum matrix have opposite expansion coefficients, there is a large stress between the interface of the negative thermal expansion phase and the aluminum matrix in the prepared composite material. When the local stress exceeds the maximum allowable stress at the location, cracks will appear, resulting in the negative thermal expansion particles being unable to effectively pull the aluminum matrix, and the expansion coefficient of the composite material increases. In the composite material prepared in this application, the particle size of the negative thermal expansion particles adjacent to the diamond phase is smaller than that of the negative thermal expansion particles far from the diamond phase. The negative thermal expansion particles with a smaller particle size increase the wettability between the aluminum liquid and the diamond phase. Secondly, part of the aluminum can react with diamond to generate Al4C3 to coordinate the stress between the negative thermal expansion particles and the aluminum matrix.

[0026] Specifically, the volume fraction of the diamond phase is 30 - 80%; the volume fraction of the negative thermal expansion ceramic phase is 10% - 40%, and the volume fraction of the aluminum matrix is at least 10%.

[0027] Specifically, the negative thermal expansion phase is one or more of ZrW2O8, Cu2P2O7, Cu2V2O7, PbTiO3, ZrMo2O8, Mn3Zn 1-x Sn x N or Mn3Zn 1-x Ge x N, where 0 < x < 1. Exemplarily, in this application, the negative expansion particles adopt ZrW2O8 and Cu2P2O7.

[0028] Specifically, the aluminum matrix is pure aluminum or aluminum alloy. The aluminum alloy includes but is not limited to Al - Mg, Al - Mn, Al - Si - Mg, Al - Mg - Zn - Cu.

[0029] Specifically, the particle size range of the negative thermal expansion particles adjacent to the diamond phase is not greater than 0.5 μm. The particle size of the negative thermal expansion particles affects their wettability between the aluminum liquid and the diamond surface on the one hand, and affects the generation of Al4C3 on the other hand, thus affecting the deformation coordination ability of the diamond phase, the aluminum matrix and the negative thermal expansion phase at the interface position. Limiting the negative thermal expansion particles within the above range can achieve the above effects.

[0030] The embodiment of the present invention also discloses a method for preparing the above-mentioned diamond and negative expansion particle reinforced aluminum-based composite material, comprising:

[0031] S1: Weigh diamond powder, negative thermal expansion particles and aluminum matrix material according to the proportion. The aluminum matrix material can be aluminum beans or aluminum blocks, and the D5 of the negative thermal expansion particles is not greater than 0.5 μm.

[0032] S2: Mix the diamond powder and the negative thermal expansion particles and place them in a graphite mold, compact them, and place the aluminum matrix material on the graphite mold. Specifically, the mixing can be carried out by ball milling, and the ball milling time should not be too long. Preferably, the material-to-ball ratio is 0.8-1.1, the ball milling speed is 200-300r / min, and the ball milling time does not exceed 10min.

[0033] S3: vacuum heating and melting the graphite mold, and then pressurizing and heat-insulating the mold after keeping the temperature for a preset time.

[0034] The vacuum heating process is as follows: the vacuum degree of the smelting furnace is ≤1Pa, the heating rate is 20-80°C / min, and the temperature is kept at Tm-Tm+150°C for 20-70min, wherein Tm is the melting point of the matrix aluminum particles.

[0035] The process of the pressurized heat preservation treatment is: using inert gas to pressurize to 0.5-2.5Mpa, and heat and pressure preservation at Tm-Tm+150°C for 10-60min, wherein Tm is the melting point of the matrix aluminum particles.

[0036] S4 is obtained by cooling after the pressurization and heat preservation treatment is completed.

[0037] The present invention can prepare negative thermal expansion particles adjacent to the diamond phase through the above process, and the particle size of the negative thermal expansion particles is smaller than the particle size of the negative thermal expansion particles away from the diamond phase. The principle is: after the aluminum matrix material is melted, it enters the gap between the diamond powder and the negative thermal expansion particles, and the small-sized negative thermal expansion particles are preferentially gathered on the surface of the aluminum liquid. With the flow of the aluminum liquid, they are likely to be brought to the surface of the diamond powder, thereby realizing the surface modification of the diamond and coordinating the stresses between the three phases. Secondly, the preparation process needs to consider the reaction between the diamond and the aluminum matrix, and try to avoid generating more Al4C3 phases. The nano-sized Al4C3 has a certain toughness and can well coordinate the deformation between the three phases. For example, the thickness of the Al4C3 phase is not more than 10nm, which has good toughness, while when the thickness is thick, the hardness is large, the brittleness is large, and the ability to coordinate deformation is weakened.

[0038] In order to better illustrate the embodiments of the present invention, the present invention is further described in detail below through specific examples.

[0039] Example 1

[0040] The embodiment of the present invention provides a diamond and negative expansion particle reinforced aluminum-based composite material and a preparation method thereof, comprising:

[0041] S1 Weigh diamond powder, ZrW2O8 particles and pure aluminum. The volume fraction of diamond powder is 50%, the volume fraction of ZrW2O8 particles is 25%, and the rest is pure aluminum; the average particle size of the diamond powder is 100 μm, the average particle size of the ZrW2O8 particles is 9.5 μm, and D5 is 0.4 μm.

[0042] S2: Mix the diamond powder and ZrW2O8 particles and place them in a graphite mold, compact them, and place the pure aluminum on top of the graphite mold.

[0043] S3: vacuum heating and melting the graphite mold, and then pressurizing and heat-insulating the mold after keeping the temperature for a preset time.

[0044] The vacuum heating process is as follows: the vacuum degree of the smelting furnace is ≤1Pa, the heating rate is 40°C / min, and the temperature is kept at 670°C for 30 minutes.

[0045] The process of the pressurized heat preservation treatment is: using inert gas to pressurize to 1.5Mpa, and keeping the temperature and pressure at 670°C for 30 minutes.

[0046] S4 is obtained by cooling after the pressurization and heat preservation treatment is completed.

[0047] The morphology of the prepared aluminum matrix composite material is shown in Figure 1 As shown, the black is the diamond phase, the white is the ZrW2O8 phase, and the gray is pure aluminum. It can be seen that the prepared diamond and negative expansion particle reinforced aluminum-based composite material has a dense structure, the negative thermal expansion phase adjacent to the diamond phase is small in size, and no cracks appear at the three-phase interface.

[0048] After measurement, the thermal conductivity of the prepared aluminum-based composite material is 679W / (m·K). Figure 2 As shown in the figure, the red color represents the linear expansion coefficient of pure aluminum. It can be seen that the aluminum-based composite material prepared in this embodiment can greatly reduce the expansion coefficient. The thermal expansion coefficient of the aluminum-based composite material prepared in this embodiment is 2.5×10 -6 / K.

[0049] Example 2

[0050] The embodiment of the present invention provides a diamond and negative expansion particle reinforced aluminum-based composite material and a preparation method thereof, comprising:

[0051] S1 Weigh diamond powder, ZrW2O8 particles and pure aluminum. The volume fraction of diamond powder is 30%, the volume fraction of ZrW2O8 particles is 10%, and the rest is pure aluminum; the average particle size of the diamond powder is 10 μm, the average particle size of the ZrW2O8 particles is 1 μm, and D5 is 0.1 μm.

[0052] S2: Mix the diamond powder and ZrW2O8 particles and place them in a graphite mold, compact them, and place the pure aluminum on top of the graphite mold.

[0053] S3: vacuum heating and melting the graphite mold, and then pressurizing and heat-insulating the mold after keeping the temperature for a preset time.

[0054] The vacuum heating process is as follows: the vacuum degree of the smelting furnace is ≤1Pa, the heating rate is 20°C / min, and the temperature is kept at 670°C for 20min.

[0055] The process of the pressurized heat preservation treatment is: using inert gas to pressurize to 0.5Mpa, and keeping the temperature and pressure at 670°C for 10 minutes.

[0056] S4 is obtained by cooling after the pressurization and heat preservation treatment is completed.

[0057] The prepared diamond and negative thermal expansion particle reinforced aluminum matrix composite material has a dense structure, the negative thermal expansion phase adjacent to the diamond phase is small in size, and no cracks appear at the three-phase interface.

[0058] After measurement, the thermal conductivity of the prepared aluminum matrix composite material is 535W / (m·K) and the thermal expansion coefficient is 5.2×10 -6 / K.

[0059] Example 3

[0060] The embodiment of the present invention provides a diamond and negative expansion particle reinforced aluminum-based composite material and a preparation method thereof, comprising:

[0061] S1 Weigh diamond powder, ZrW2O8 particles and pure aluminum. The volume fraction of diamond powder is 70%, the volume fraction of ZrW2O8 particles is 10%, and the rest is pure aluminum; the average particle size of the diamond powder is 900 μm, the average particle size of the ZrW2O8 particles is 50 μm, and D5 is 0.5 μm.

[0062] S2: Mix the diamond powder and ZrW2O8 particles and place them in a graphite mold, compact them, and place the pure aluminum on top of the graphite mold.

[0063] S3: vacuum heating and melting the graphite mold, and then pressurizing and heat-insulating the mold after keeping the temperature for a preset time.

[0064] The vacuum heating process is as follows: the vacuum degree of the smelting furnace is ≤1Pa, the heating rate is 80°C / min, and the temperature is kept at 670°C for 70min.

[0065] The process of the pressurized heat preservation treatment is: using inert gas to pressurize to 2.5Mpa, and keeping the temperature and pressure at 670°C for 60 minutes.

[0066] S4 is obtained by cooling after the pressurization and heat preservation treatment is completed.

[0067] The prepared diamond and negative thermal expansion particle reinforced aluminum matrix composite material has a dense structure, the negative thermal expansion phase adjacent to the diamond phase is small in size, and no cracks appear at the three-phase interface.

[0068] After measurement, the thermal conductivity of the prepared aluminum matrix composite material is 694W / (m·K) and the thermal expansion coefficient is 3.1×10 -6 / K.

[0069] Example 4

[0070] Different from Example 1, in step S1 of this embodiment, the average particle size of the Cu2P2O7 particles is 10 μm and D5 is 0.1 μm.

[0071] The prepared diamond and negative expansion particle reinforced aluminum matrix composite material has a dense structure, the negative thermal expansion phase adjacent to the diamond phase is small in size, and no cracks appear at the three-phase interface when the reduction rate is 20%.

[0072] After measurement, the thermal conductivity of the prepared aluminum matrix composite material is 526W / (m·K), and the thermal expansion coefficient is 3.19×10 -6 / K.

[0073] Comparative Example 1

[0074] Different from Example 1, in step S1 of this comparative example, the D5 of the ZrW2O8 particles is 0.7 μm.

[0075] The prepared diamond and negative expansion particle reinforced aluminum matrix composite material had cracks between the diamond phase and the aluminum matrix when the reduction rate was 20%. When the D5 particle size was large, the diamond surface could not be effectively modified, resulting in poor bonding between the diamond phase and the aluminum matrix.

[0076] Comparative Example 2

[0077] Different from Example 1, in step S1 of this comparative example, the average particle size of the diamond powder is 100 μm, the average particle size of the ZrW2O8 particles is 4 μm, and D5 is 0.1 μm.

[0078] The prepared diamond and negative thermal expansion particle reinforced aluminum matrix composite material has poor microstructure uniformity, and cracks appear at the three-phase interface when the reduction rate is 20%. Due to the large difference in particle size between diamond powder and negative thermal expansion particles, the smaller negative thermal expansion particles are deposited at the bottom, while the larger particles are deposited at the top, resulting in uneven microstructure.

[0079] Comparative Example 3

[0080] Different from Example 2, in step S3 of this comparative example, the temperature is kept at 670° C. for 100 min.

[0081] When the reduction rate of the prepared diamond and negative expansion particle reinforced aluminum matrix composite material was 20%, cracks occurred between the diamond phase and the aluminum matrix. The reason was that the generated Al4C3 phase was too much and too thick, resulting in a weakened deformation coordination ability.

[0082] Comparative Example 4

[0083] Different from Example 1, in step S3 of this comparative example, the temperature is kept at 670° C. for 15 minutes.

[0084] The prepared diamond and negative expansion particle reinforced aluminum matrix composite material has pores in its microstructure. When the reduction rate of the prepared diamond and negative expansion particle reinforced aluminum matrix composite material is 20%, cracks are generated between the diamond phase and the aluminum matrix.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A diamond and negative expansion particle reinforced aluminum matrix composite material, characterized in that: The aluminum-based composite material consists of a diamond phase and a negative thermal expansion phase dispersed in an aluminum matrix; the average particle size of the diamond phase is 10-1000 μm, and the ratio of the average particle size of the diamond phase to the average particle size of the negative thermal expansion particles is 10-20; The particle size of the negative thermal expansion particles adjacent to the diamond phase is smaller than the particle size of the negative thermal expansion particles away from the diamond phase.

2. The diamond and negative expansion particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The volume fraction of the diamond phase is 30-80%; the volume fraction of the negative thermal expansion ceramic phase is 10%-40%; and the volume fraction of the aluminum matrix is ​​at least 20%.

3. The diamond and negative expansion particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The negative thermal expansion phase is ZrW2O8, Cu2P2O7, Cu2V2O7, PbTiO3, ZrMo2O8, Mn3Zn 1-x Sn x N or Mn3Zn 1-x Ge x One or more of N, 0 <x<1。 4. The diamond and negative expansion particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The aluminum matrix is ​​pure aluminum or aluminum alloy.

5. The diamond and negative expansion particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The particle size range of the negative thermal expansion particles adjacent to the diamond phase is no greater than 0.5 μm.

6. The method for preparing the diamond and negative expansion particle reinforced aluminum-based composite material according to any one of claims 1 to 5, characterized in that: Weigh diamond powder, negative thermal expansion particles and aluminum matrix material according to proportion; The diamond powder and the negative thermal expansion particles are mixed and placed in a graphite mold, compacted by vibration, and the aluminum matrix material is placed on top of the graphite mold; The graphite mold is melted by vacuum heating, and then pressurized and kept warm for a preset time; After the pressurization and heat preservation treatment is completed, cool it down.

7. The preparation method according to claim 6, characterized in that: The average particle size of the diamond powder is 10-1000 μm; the ratio of the average particle size of the diamond phase to the average particle size of the negative thermal expansion particles is 10-20.

8. The preparation method according to claim 6, characterized in that: The negative thermal expansion particles have a D5 value of no greater than 0.5 μm.

9. The preparation method according to claim 6, characterized in that: The vacuum heating process is as follows: the vacuum degree of the melting furnace is ≤1Pa, the heating rate is 20-80°C / min, and the temperature is kept at Tm-Tm+150°C for 20-70min, wherein Tm is the melting point of the aluminum matrix.

10. The preparation method according to claim 6, characterized in that: The process of the pressurized heat preservation treatment is: using inert gas to pressurize to 0.5-2.5Mpa, and keeping the temperature and pressure at Tm-Tm+150°C for 10-60min, wherein Tm is the melting point of the aluminum matrix.

Citation Information

Patent Citations

  • Preparation method of diamond-reinforced aluminum-based high-thermal-conductivity composite material

    CN114411010A

  • Preparation method of high-performance diamond reinforced Al-matrix electronic packaging composite material

    CN101728279A

  • Preparation method of diamond / aluminum composite material for reducing thermal expansion coefficient by using negative expansion material

    CN119491137A

  • Diamond composite heat spreader and associated methods

    US20040070071A1

  • High thermal conductivity metal matrix composites

    US20050074355A1

Cited By

  • Corrosion-resistant aluminum / diamond composite material as well as preparation method and application thereof

    CN121496251A